2014
DOI: 10.3906/muh-1404-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and recovery of contaminated railway ballast

Abstract: Experimental tests of metal extraction from stones sampled from artificially contaminated railway ballasts are presented and discussed. Metal extraction was performed by washing with aqueous solutions of disodium ethylenediaminetetraacetate (EDTA), at selected concentrations. The effectiveness of the remediation process was evaluated using leaching tests.The results indicate that the washing technology represents a successful and affordable solution for the implementation of an on-site treatment aimed at a reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Di Palma & Petrucci [2014] showed that only a slight release of Cu and Zn was observed for the uncontaminated ballast stones. The Cd concentration in the leachate was always below the a) b) Fig.…”
Section: Heavy Metal Content In Railway Stones After Washingmentioning
confidence: 99%
“…Di Palma & Petrucci [2014] showed that only a slight release of Cu and Zn was observed for the uncontaminated ballast stones. The Cd concentration in the leachate was always below the a) b) Fig.…”
Section: Heavy Metal Content In Railway Stones After Washingmentioning
confidence: 99%
“…The various parameters that signicantly affect the production of biosurfactants using palm oil and coconut oil as substrates, such as time (24-120 h), pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), temperature (20-50 C) and concentration of substrate (10-60 g L À1 ), were optimized using one parameter at a time while the other parameters were kept constant. The most signicant range of parameters was further optimized using Response Surface Methodology (RSM) for the production of the biosurfactant.…”
Section: Optimization Studies For the Production Of Biosurfactantsmentioning
confidence: 99%
“…5 Cr(III) tends to be strongly bound by soil humic acid polymers, and this affinity restricts the availability of Cr(III) to be oxidized and reduces the decomposition of organic matter. 6 Cr(III) in soils could be leached into surface water or groundwater and be absorbed by plants. 5 Chromium(III) enters the human food chain through the consumption of the vegetative plants.…”
Section: Introductionmentioning
confidence: 99%
“…102 In addition, for metal pollution, a washing test aimed at metal extraction from stones sampled from artificially contaminated railway ballasts is presented and discussed. 103 Metal extraction was performed by washing with aqueous solutions.…”
Section: Ballast Fouling Preventionmentioning
confidence: 99%